LEGAL PROTECTION AGAINST VICTIMS OF BULLYING IN THE COMMUNITY OF DENAI LAMA VILLAGE - Harlan Perdana Pasaribu; Padian Adi Salamat Siregar (NOMOI Law Review, 2022)
Bullying is not a new crime in society, Bullying cannot be underestimated considering the most dangerous impact of Bullying, which can cause a person to have a desire to commit suicide. Therefore, the protection provided by law is needed so that the crime of bullying in the community can be reduced. Most of the bullying behavior is now carried out by small children, as I found at the KKN location at this time the victim was getting bullied from his peers, when I did the counseling, the victim had told me that he had often received bullying behavior ( bullying), for example the victim told me that the victim received a blow to the head. And the victim said that the perpetrator also bullied again during the ceremony, the victim experienced vomiting due to encouragement from the perpetrator for the victim during the August 17, 2022 Ceremony at school. The method used in this paper is normative legal research. With me conducting counseling about bullying material, it is hoped that in the future it will greatly help the surrounding environment so that there are fewer bullies like what is happening at this location.